Determinants in nonstructural protein 4A of dengue virus required for RNA replication and replication organelle biogenesis - Cortese, Mirko; Mulder, Klaas; Chatel-Chaix, Laurent; Scaturro, Pietro; Cerikan, Berati; Plaszczyca, Anna; Haselmann, Uta; Bartenschlager, Marie; Neufeldt, Christopher; Bartenschlager, Ralf (Journal of virology, 2021)
Dengue virus (DENV) constitutes one of the most important arboviral pathogens affecting humans. The high prevalence of DENV infections, which cause more than 20,000 deaths annually, and the lack of effective vaccines or direct-acting antiviral drugs make it a global health concern. DENV genome replication occurs in close association with the host endomembrane system, which is remodeled to form the viral replication organelle that originates from endoplasmic reticulum (ER) membranes. To date, the viral and cellular determinants responsible for the biogenesis of DENV replication organelles are still poorly defined. The viral nonstructural protein 4A (NS4A) can remodel membranes and has been shown to associate with numerous host factors in DENV-replicating cells. In the present study, we used reverse and forward genetic screens and identified sites within NS4A required for DENV replication. We also mapped the determinants in NS4A required for interactions with other viral proteins. Moreover, taking advantage of our recently developed polyprotein expression system, we evaluated the role of NS4A in the formation of DENV replication organelles. Together, we report a detailed map of determinants within NS4A required for RNA replication, interaction with other viral proteins, and replication organelle formation. Our results suggest that NS4A might be an attractive target for antiviral therapy.